Cheah Boon Kheng (1939–2015) in Memoriam - Abu Talib Ahmad (Kajian Malaysia, 2017)
Cheah Boon Kheng was already a well known historian when I first met him at the staff canteen within the School of Humanities/Social Sciences in early 1985. I had reported for duty in early December the previous year but he was away in Yale University as a Fullbright Visiting Research Fellow. His impeccable reputation notably among international scholars was contributed by the two books, the Masked Comrades: A Study of the Communist United Front in Malaya, 1945–48 (1979) and Red Star Over Malaya: Resistance and Social Conflict during and after the Japanese Occupation, 1941–46 (1983) which have received critical reviews among scholars of Southeast Asia. By the first decade of the 21st century he had written three more books The Peasant Robber of Kedah, 1900–1929: Historical and Folk Perceptions (1988), To' Janggut: Legends, Histories and Perceptions of the 1915 Rebellion in Kelantan (2006), and Malaysia: The Making of a Nation (2002). In addition, he had also edited a number of major works and essays, many of which were published in the Journal of the Malaysian Branch of the Royal Asiatic Society (JMBRAS), covering various aspects of Malaysian history that have been widely consulted. A few of these books such as Red Star over Malaya, the Peasant Robbers of Kedah and To'Janggut went through several editions. Although I was not aware of who Boon Kheng was during our first encounter, which was facilitated by another senior colleague, the late R. Suntharalingam, it marked the beginning of a fruitful relationship that went beyond Boon Kheng's retirement from Universiti Sains Malaysia (USM) in 1994 as professor of Malaysian history. He had joined the university in 1978 after completing his MA at the University of Malaya. Within the History Section we got along well as attested by the two books we edited together in 1990 and 1995. With his encouragement, I organised a course on the Japanese Occupation of Southeast Asia which was well subscribed as it involved the use of oral history. At one point both of us were elected as members of the university senate by the School of Humanities and some of the issues we raised in senate proceedings were the small funding allocated for research in the humanities and social sciences compared to the sciences.